Analysis of Research Ethics Board Approval Times in an Academic Department of Medicine. (April 2015) - Tsang, Teresa S. M.; Jones, Meaghan; Meneilly, Graydon S.
As part of an ongoing effort to better understand barriers to academic research, we reviewed and analyzed the process of research ethics applications, focusing on ethics approval time, within the Department of Medicine from 2006 to 2011. A total of 1, 268 applications for approval to use human subjects in research were included in our analysis. Three variables, risk category (minimal vs. non-minimal risk), type of funding, and year of submission, were statistically significant for prediction of ethics approval time, with risk status being the most important of these. The covariate-adjusted mean time for approval for minimal risk studies (35.7 days) was less than half that of non-minimal risk protocols (76.5 days). Studies funded through a for-profit sponsor had significantly longer approval times than those funded through other means but were also predominantly (87%) non-minimal risk protocols. Further investigations of the reasons underlying the observed differences are needed to determine whether improved training for research ethics board (REB) members and/or greater dialogue with investigators may reduce the lengthy approval times associated with non-minimal risk protocols.